All-solid-state battery
By combining different reduction-resistant sulfide solid electrolytes in the solid electrolyte layer of an all-solid battery and forming a LiM alloy protective layer, the problem of simplifying the battery structure and improving the cycle characteristics in the prior art is solved, and efficient energy density and cycle stability are achieved.
Patent Information
- Application Number
- CN202410987220.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2024-07-23
- Publication Date
- 2025-03-07
AI Technical Summary
While improving the energy density and battery performance, existing all-solid batteries are difficult to take into account the simplification of the battery structure and the improvement of cycle characteristics.
The solid electrolyte layer A is used to combine the first sulfide solid electrolyte with relatively low reduction resistance and the second sulfide solid electrolyte with relatively high reduction resistance in the solid electrolyte layer A, and a third sulfide solid electrolyte with high reduction resistance is used in the solid electrolyte layer B to protect the decomposition of the sulfide solid electrolyte by forming a LiM alloy as a protective layer.
The simplification of the battery structure and the improvement of the cycle characteristics are achieved, and the capacity maintenance rate and cycle stability of the battery are improved.
Smart Images

Figure CN119581646A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to all-solid-state batteries. Background Art
[0002] All-solid batteries are batteries having a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer, and have the advantage of being easy to simplify safety devices compared to liquid batteries having an electrolyte solution containing a flammable organic solvent. In addition, in the field of all-solid batteries, batteries that use the precipitation and dissolution reaction of metallic lithium as the negative electrode reaction are known.
[0003] For example, Japanese Patent Application Laid-Open No. 2021-89814 discloses an all-solid-state battery using the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction. The all-solid-state battery sequentially comprises a negative electrode collector, a Li absorption layer comprising a spherical carbon material and a resin, a metal M layer comprising a metal M alloyable with lithium, a solid electrolyte layer, and a positive electrode layer, wherein the thickness of the metal M layer is greater than 30 nm and less than 5 μm. Summary of the invention
[0004] In an all-solid-state battery that utilizes the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction, generally, when making an all-solid-state battery, a general negative electrode active material layer is not provided, but a negative electrode active material layer (Li-containing layer) is formed by initial charging. Therefore, the all-solid-state battery has the advantages of being easy to simplify the manufacturing process and easy to improve the energy density. A general negative electrode active material layer is a layer containing negative electrode active material particles that absorb and release Li. On the other hand, from the viewpoint of improving energy density and improving battery performance, an all-solid-state battery that takes into account both the simplification of the battery structure and the improvement of the cycle characteristics is required.
[0005] The present disclosure has been completed in view of the above-mentioned actual situation, and its main purpose is to provide an all-solid-state battery that combines simplification of the battery structure with improvement of the cycle characteristics.
[0006] The all-solid-state battery according to one embodiment of the present disclosure is an all-solid-state battery that utilizes the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction, and has a negative electrode collector, a solid electrolyte layer A, a solid electrolyte layer B, and a positive electrode active material layer in the thickness direction, wherein the solid electrolyte layer A contains a first sulfide solid electrolyte and a second sulfide solid electrolyte, and the solid electrolyte layer B contains a third sulfide solid electrolyte, wherein the first sulfide solid electrolyte is a sulfide solid electrolyte that is 0.3V (vsLi / Li) in a cyclic voltammetry measurement. + ) and above 1.0V(vsLi / Li +) or less, and contains an M element, M is at least one of Sn, Al, Zn, In, Ge, Si, Sb, Ga and Bi, and the second sulfide solid electrolyte is at 0.3V (vsLi / Li in cyclic voltammetry) + ) and above 1.0V(vsLi / Li + ) or less and having no reduction reaction peak, wherein in the solid electrolyte layer A, the ratio of the first sulfide solid electrolyte is greater than 0 weight % and less than 45 weight % relative to the total weight of the first sulfide solid electrolyte and the second sulfide solid electrolyte.
[0007] In the all-solid-state battery of the above embodiment, in the solid electrolyte layer A, the ratio of the first sulfide solid electrolyte to the total weight of the first sulfide solid electrolyte and the second sulfide solid electrolyte may be 5 wt % or more and 40 wt % or less.
[0008] In the all-solid battery of the above scheme, the third sulfide solid electrolyte may be a cyclic voltammetry measurement at 0.3V (vsLi / Li + ) and above 1.0V(vsLi / Li + ) or less sulfide solid electrolyte having no reduction reaction peak.
[0009] In the all-solid-state battery of the above embodiment, the first sulfide solid electrolyte may contain Li element, the M element, and S element, and the M element is at least one of Sn, Al, Zn and In.
[0010] In the all-solid-state battery of the above embodiment, the all-solid-state battery may include a protective layer containing Li and M between the negative electrode collector and the solid electrolyte layer A.
[0011] The all-solid-state battery disclosed herein achieves the effect of being able to achieve both simplification of the battery structure and improvement of the cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:
[0013] Figure 1 A schematic cross-sectional view illustrating an all-solid-state battery of the present disclosure;
[0014] Figure 2 A schematic cross-sectional view illustrating an all-solid-state battery of the present disclosure;
[0015] Figure 3A schematic cross-sectional view illustrating an all-solid-state battery of the present disclosure; and
[0016] Figure 4 The results are as follows for the capacity retention rates of the battery cells prepared in Examples 1 to 3, Comparative Examples 1 to 5, and Reference Examples 1 to 3. DETAILED DESCRIPTION
[0017] The all-solid-state battery of the present disclosure is described in detail below using the accompanying drawings. The following drawings are schematic illustrations, and the size and shape of each part are exaggerated as appropriate for easier understanding.
[0018] Figure 1 and Figure 2 2 is a schematic cross-sectional view illustrating an all-solid-state battery disclosed herein. More specifically, Figure 1 An example of an all-solid-state battery before initial charge. Figure 2 An all-solid-state battery after initial charge is shown. Figure 1 The all-solid-state battery 10 shown in FIG. T The structure of the present invention is provided with a negative electrode current collector 1, a solid electrolyte layer 2A (solid electrolyte layer A), a solid electrolyte layer 2B (solid electrolyte layer B), a positive electrode active material layer 3 and a positive electrode current collector 4 in this order. The solid electrolyte layer 2A contains a first sulfide solid electrolyte having relatively low reduction resistance and a second sulfide solid electrolyte having relatively high reduction resistance in a predetermined ratio. In addition, the solid electrolyte layer 2B contains a third sulfide solid electrolyte. On the other hand, as Figure 2 As shown, Figure 1 When the all-solid-state battery 10 shown is charged, a protective layer 5 containing Li and M (specific metal element contained in the first sulfide solid electrolyte) is formed between the negative electrode current collector 1 and the solid electrolyte layer 2A.
[0019] In the present disclosure, in a battery utilizing the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction, two sulfide solid electrolytes such as a first sulfide solid electrolyte with relatively low reduction resistance and a second sulfide solid electrolyte with relatively high reduction resistance are used in the solid electrolyte layer A. As a result, the battery of the present disclosure becomes a fully solid battery that takes into account both the simplification of the battery structure and the improvement of the cycle characteristics. In addition, the solid electrolyte layer has a solid electrolyte layer A and a solid electrolyte layer B, and the solid electrolyte layer A contributes greatly to the improvement of the cycle characteristics. As a result, the range of material selection for the solid electrolyte layer B becomes wider, for example, by selecting a third sulfide solid electrolyte with relatively high reduction resistance, the cycle characteristics can be further improved. Generally, if the sulfide solid electrolyte is reduced and decomposed, the ion conductivity is significantly reduced, so for the sulfide solid electrolyte used for the solid electrolyte layer, a material with high reduction resistance is used. In particular, in a battery utilizing the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction, for example, compared with a battery using a graphite-based active material as a negative electrode active material, a sulfide solid electrolyte with excellent reduction resistance has been used in the past because the reaction potential of the negative electrode is low.
[0020] In the present disclosure, in addition to the sulfide solid electrolyte (second sulfide solid electrolyte) with excellent reduction resistance, a sulfide solid electrolyte (first sulfide solid electrolyte) with lower reduction resistance than the second sulfide solid electrolyte is used in a prescribed ratio. By using the first sulfide solid electrolyte and the second sulfide solid electrolyte in combination, unexpectedly, an excellent effect of improving the cycle characteristics is obtained compared with the case where the second sulfide solid electrolyte with excellent reduction resistance is used alone. As a reason for the improvement in cycle characteristics, it is speculated that the reason is that the first sulfide solid electrolyte contains a specific M element, and a LiM alloy is generated as a decomposition product of the first sulfide solid electrolyte, and the generated LiM alloy functions as a protective layer. The protective layer protects the decomposition of the sulfide solid electrolyte. In addition, by forming a protective layer from the first sulfide solid electrolyte, the solid electrolyte layer is protected, so it is no longer necessary to set other protective layers, or the thickness of other protective layers can be made thinner. Therefore, it is possible to take into account both the simplification of the battery structure and the improvement of the cycle characteristics.
[0021] 1. Solid electrolyte layer
[0022] The solid electrolyte layer includes, in order from the negative electrode current collector side, a solid electrolyte layer A and a solid electrolyte layer B. The solid electrolyte layer A and the solid electrolyte layer B are generally layers having different compositions.
[0023] (1) Solid electrolyte layer A
[0024] The solid electrolyte layer A contains a first sulfide solid electrolyte and a second sulfide solid electrolyte as sulfide solid electrolytes. The sulfide solid electrolyte is generally a solid electrolyte containing sulfur (S) as a main component of an anion element.
[0025] (i) First sulfide solid electrolyte
[0026] The first sulfide solid electrolyte is a sulfide solid electrolyte having lower reduction resistance than the second sulfide solid electrolyte described later. Specifically, the first sulfide solid electrolyte has a cyclic voltammetry measurement at 0.3 V (vs Li / Li + ) and above 1.0V(vsLi / Li + ) has a reduction reaction peak below. At a potential of 0.3 V (vs Li / Li + ) and above 1.0V(vsLi / Li + ) or less, a reduction reaction usually occurs due to the metal element M described later. In the case where the first sulfide solid electrolyte contains a P element as a non-metallic element, at a potential ratio of 1.0 V (vsLi / Li + ) at high potentials, a reduction reaction caused by the P element may occur. In order to eliminate the influence of the P element, the upper limit is set to 1.0V (vsLi / Li + The details of the cyclic voltammetry measurement will be described in the examples described later.
[0027] The first sulfide solid electrolyte may be a glass-based (amorphous) sulfide solid electrolyte, a glass-ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte.
[0028] The first sulfide solid electrolyte usually contains Li element, M element (M is at least one of Sn, Al, Zn, In, Ge, Si, Sb, Ga and Bi), and S element. Any of the M elements is an element that can be alloyed with Li. The first sulfide solid electrolyte preferably also contains P element. In addition, the first sulfide solid electrolyte may contain halogen elements such as F, Cl, Br, and I. In addition, in the first sulfide solid electrolyte, a part of the S element may be replaced by the O element.
[0029] The first sulfide solid electrolyte may have a crystal phase. Examples of the crystal phase include an LGPS type crystal phase, a Thio-LISICON type crystal phase, and an Argentum type crystal phase.
[0030] The composition of the first sulfide solid electrolyte is not particularly limited, and examples thereof include Li 4-x Sn 1-x P xS4 (0<x<1). At least a portion of Sn may be replaced by at least one of Al, Zn, In, Ge, Si, Sb, Ga and Bi. Similarly, at least a portion of P may be replaced by at least one of Al, Zn, In, Ge, Si, Sb, Ga and Bi. In addition, a portion of Li may be replaced by at least one of Na, K, Mg, Ca and Zn. Furthermore, a portion of S may be replaced by halogen (F, Cl, Br, I) or by oxygen (O).
[0031] As another example of the composition of the first sulfide solid electrolyte, xLi2S-(1-x)SnS2-yLiX (0<x<1, 0≤y<1, X is one or more halogens) can be listed. At least a portion of Sn can be replaced by at least one of Al, Zn, In, Ge, Si, Sb, Ga and Bi. In addition, a portion of Li can be replaced by at least one of Na, K, Mg, Ca and Zn. Furthermore, a portion of S can be replaced by oxygen (O).
[0032] The first sulfide solid electrolyte is in the form of particles, for example. The average particle size of the first sulfide solid electrolyte is, for example, 0.5 μm or more and 30 μm or less. In the present disclosure, the average particle size refers to the volume cumulative particle size D measured by a laser diffraction scattering particle size distribution measuring device. 50 .
[0033] (ii) Second sulfide solid electrolyte
[0034] The second sulfide solid electrolyte is a sulfide solid electrolyte having a higher reduction resistance than the first sulfide solid electrolyte. Specifically, the second sulfide solid electrolyte has a cyclic voltammetry measurement at 0.3 V (vs Li / Li + ) and above 1.0V(vsLi / Li + ) and below do not have a reduction reaction peak.
[0035] The second sulfide solid electrolyte may be a glass-based (amorphous) sulfide solid electrolyte, a glass-ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte.
[0036] The second sulfide solid electrolyte usually contains at least Li and S. The second sulfide solid electrolyte preferably further contains P. In addition, the second sulfide solid electrolyte may contain halogen elements such as F, Cl, Br, and I. In addition, the second sulfide solid electrolyte may contain O. In addition, the second sulfide solid electrolyte preferably does not contain metal elements other than Li, but may contain metal elements other than Li as long as it does not affect the reduction resistance.
[0037] The second sulfide solid electrolyte may have a crystal phase. Examples of the crystal phase include a Thio-LISICON type crystal phase, an Argentum type crystal phase, and an LGPS type crystal phase.
[0038] There is no particular limitation on the composition of the second sulfide solid electrolyte. However, the composition of the second sulfide solid electrolyte may be, for example, xLi2S·(1-x)P2S5(0.5≤x<1), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.5≤x<1, 0≤y≤30, 0≤z≤30). In these compositions, x preferably satisfies 0.7≤x≤0.8. In addition, in these compositions, a portion of Li may be replaced by at least one of Na, K, Mg, Ca and Zn. Furthermore, a portion of S may be replaced by oxygen (O).
[0039] Another example of the composition of the second sulfide solid electrolyte is Li 7-x-2y PS 6-x-y X y X is at least one of F, Cl, Br, and I, and x and y satisfy 0≤x, 0≤y. A portion of Li may be replaced by at least one of Na, K, Mg, Ca, and Zn. Furthermore, a portion of S may be replaced by oxygen (O).
[0040] The second sulfide solid electrolyte is in the form of particles, for example. The average particle size of the second sulfide solid electrolyte is, for example, 0.5 μm or more and 30 μm or less.
[0041] (iii) Solid electrolyte layer A
[0042] The solid electrolyte layer A contains a first sulfide solid electrolyte and a second sulfide solid electrolyte. In the solid electrolyte layer A, it is preferred that the first sulfide solid electrolyte and the second sulfide solid electrolyte are uniformly dispersed. In addition, in the solid electrolyte layer A, the ratio of the first sulfide solid electrolyte relative to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte is greater than 0% by weight and less than 45% by weight. The above ratio of the first sulfide solid electrolyte may be 1% by weight or more, 3% by weight or more, or 5% by weight or more. On the other hand, the above ratio of the first sulfide solid electrolyte may be 40% by weight or less, or 30% by weight or less. In addition, the above ratio of the first sulfide solid electrolyte may be about 10% by weight (5% by weight or more and 15% by weight or less). In addition, in the solid electrolyte layer A, the total ratio of the first sulfide solid electrolyte and the second sulfide solid electrolyte is, for example, 80% by weight or more, 90% by weight or more, or 95% by weight or more.
[0043] The solid electrolyte layer A may contain a binder. Examples of the binder include rubber-based binders such as butene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVDF). The thickness of the solid electrolyte layer A is, for example, 0.5 μm or more and 250 μm or less.
[0044] (2) Solid electrolyte layer B
[0045] The solid electrolyte layer B contains a third sulfide solid electrolyte as the sulfide solid electrolyte. The solid electrolyte layer B may contain one third sulfide solid electrolyte or two or more third sulfide solid electrolytes.
[0046] The third sulfide solid electrolyte may be a solid electrolyte having a cyclic voltammetry value of 0.3 V (vs Li / Li) similarly to the first sulfide solid electrolyte. + ) and above 1.0V(vsLi / Li + ) or less. On the contrary, the solid electrolyte layer B may not contain the sulfide solid electrolyte α.
[0047] The third sulfide solid electrolyte may be a solid electrolyte having a cyclic voltammetry value of 0.3 V (vs Li / Li) similarly to the second sulfide solid electrolyte. + ) and above 1.0V(vsLi / Li + ) or less. On the contrary, the solid electrolyte layer B may not contain the sulfide solid electrolyte β.
[0048] The solid electrolyte layer B may contain both the sulfide solid electrolyte α and the sulfide solid electrolyte β as a third sulfide solid electrolyte. In this case, the ratio of the sulfide solid electrolyte α to the total of the sulfide solid electrolyte α and the sulfide solid electrolyte β is defined as R B In the solid electrolyte layer A, the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte is denoted by R A (wt%). A R B Big. R A and R B The difference is preferably, for example, 3% by weight or more.
[0049] The third sulfide solid electrolyte may be a glass (amorphous) sulfide solid electrolyte, a glass ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. The details of the third sulfide solid electrolyte are the same as those described in the first sulfide solid electrolyte and the second sulfide solid electrolyte.
[0050] Solid electrolyte layer B may be composed of a single layer or a plurality of layers. Among the entire solid electrolyte layer, one or more solid electrolyte layers located on the positive electrode side relative to solid electrolyte layer A correspond to solid electrolyte layer B.
[0051] In the solid electrolyte layer B, the proportion of the third sulfide solid electrolyte is, for example, 80% by weight or more, 90% by weight or more, or 95% by weight or more. In addition, the solid electrolyte layer B may contain an adhesive. As an adhesive, for example, rubber-based adhesives such as butene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based adhesives such as polyvinylidene fluoride (PVDF) can be listed. In addition, the thickness of the solid electrolyte layer B is, for example, 0.5 μm or more and 250 μm or less. In addition, the thickness of the solid electrolyte layer B is, for example, 1.0 times or more, 1.5 times or more, or 2.0 times or more relative to the thickness of the solid electrolyte layer A.
[0052] 2. Positive electrode
[0053] The positive electrode in the present disclosure has a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer contains at least a positive electrode active material. In addition, the positive electrode active material layer may contain at least one of a solid electrolyte, a conductive material, and a binder.
[0054] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCOO2, LiNi 1 / 3 CO 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials; LiMn2O4, Li4Ti5O 12 Spinel-type active materials such as LiFePO4; olivine-type active materials such as LiFePO4.
[0055] As the conductive material, for example, a carbon material can be cited. As the carbon material, for example, a particulate carbon material such as acetylene black (AB) and Ketjen black (KB); a fibrous carbon material such as carbon fiber, carbon nanotube (CNT) and carbon nanofiber (CNF). In addition, the solid electrolyte and the binder are the same as those described in the above "1. Solid electrolyte layer".
[0056] Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, and carbon. Examples of the shape of the positive electrode current collector include a foil shape. The thickness of the positive electrode current collector is, for example, 1 μm or more and 500 μm or less.
[0057] 3. Negative electrode
[0058] The negative electrode in the present disclosure has at least a negative electrode current collector. Figure 3As shown, the negative electrode 1 may include, for example, a Mg layer 6 described later. On the other hand, the negative electrode preferably does not include a negative electrode active material layer containing negative electrode active material particles.
[0059] Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. Examples of the shape of the negative electrode current collector include a foil shape. The thickness of the negative electrode current collector is, for example, 1 μm or more and 500 μm or less.
[0060] like Figure 1 As shown, the negative electrode current collector 1 may be in direct contact with the solid electrolyte layer 2A. Figure 3 As shown, an Mg layer containing Mg may be arranged between the negative electrode current collector 1 and the solid electrolyte layer 2A. By providing the Mg layer, the cycle characteristics become better. The Mg layer may contain Mg metal (Mg single substance) or Mg alloy (alloy with Mg as the main component).
[0061] The Mg layer is preferably in close contact with the negative electrode collector. That is, the Mg layer is preferably configured in a manner that covers the surface of the negative electrode collector. In the present disclosure, a component having a negative electrode collector and a Mg layer configured on the negative electrode collector is sometimes referred to as a coated collector. In the coated collector, the Mg layer and the negative electrode collector may be in direct contact or may be configured via other layers. On the other hand, the Mg layer and the solid electrolyte layer A may be in direct contact or may be configured via other layers.
[0062] The Mg layer is, for example, a thin film, preferably a vapor-deposited film. The thickness of the Mg layer is not particularly limited, and is, for example, 30 nm or more. On the other hand, the thickness of the Mg layer may be, for example, 2000 nm or less, or 1500 nm or less. In addition, the Mg layer may be formed by, for example, a vapor deposition method such as vacuum vapor deposition.
[0063] The Mg layer may contain no Li or may contain Li. The former is equivalent to the state of the Mg layer in the all-solid battery before the initial charge, and the latter is equivalent to the state of the Mg layer in the all-solid battery after the initial charge. Through the initial charge, Li is introduced into the Mg layer, and the Mg contained in the Mg layer is alloyed with Li. As a result, an alloy phase such as a Mg-Li alloy phase is formed in the Mg layer. On the other hand, during discharge, Li moves from the Mg layer alloyed with Li to the positive electrode side. In addition, although not specifically shown in the figure, the above-mentioned protective layer can be configured between the Mg layer and the solid electrolyte layer A. In addition, a Li phase can be formed inside the Mg layer. In addition, a precipitated Li layer can be formed between the Mg layer and the solid electrolyte layer A. In addition, a precipitated Li layer can be formed between the Mg layer and the negative electrode collector.
[0064] 4. All-solid-state batteries
[0065] like Figure 2As shown, the all-solid-state battery 10 may have a protective layer 5 containing Li and the above-mentioned M (M is at least one of Sn, Al, Zn, In, Ge, Si, Sb, Ga and Bi) between the negative electrode collector 1 and the solid electrolyte layer 2A. The protective layer 5 generally contains an alloy phase such as a LiM alloy phase. The protective layer 5 may contain residual components of a sulfide solid electrolyte. As residual components of a sulfide solid electrolyte, for example, compounds containing P elements and Li elements, and compounds containing S elements and Li elements (for example, Li2S) can be listed. In addition, there is no particular limitation on the thickness of the protective layer, for example, it is greater than 5 nm and less than 100 nm. In addition, a Li phase can be formed inside the protective layer. In addition, a precipitated Li layer can be formed between the protective layer and the solid electrolyte layer A. In addition, a precipitated Li layer can be formed between the protective layer and the negative electrode collector.
[0066] The use of the all-solid-state battery in the present disclosure is not particularly limited, for example, power sources for vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), battery electric vehicles (BEV), gasoline vehicles, and diesel vehicles can be listed. It is particularly preferred to be used as a driving power source for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) or battery electric vehicles (BEV). In addition, the all-solid-state battery can be used as a power source for mobile bodies other than vehicles (such as railways, ships, and aircraft), and can also be used as a power source for electrical products such as information processing devices.
[0067] In addition, the present disclosure can also provide a method for manufacturing the above-mentioned all-solid-state battery. Specifically, the present disclosure can also provide a method for manufacturing an all-solid-state battery having a preparation process and a charging process. In the preparation process, an all-solid-state battery before the initial charge is prepared, which has a negative electrode collector, a solid electrolyte layer A, a solid electrolyte layer B and a positive electrode active material layer in sequence in the thickness direction. In the charging process, the all-solid-state battery before the initial charge is charged. The above-mentioned solid electrolyte layer A contains a first sulfide solid electrolyte and a second sulfide solid electrolyte. The above-mentioned solid electrolyte layer B contains a third sulfide solid electrolyte. The above-mentioned first sulfide solid electrolyte is a solid electrolyte that is 0.3V (vsLi / Li in a cyclic voltammetry measurement). + ) and above 1.0V(vsLi / Li + ) or less. In addition, the first sulfide solid electrolyte contains an M element (M is at least one of Sn, Al, Zn, In, Ge, Si, Sb, Ga and Bi). The second sulfide solid electrolyte is a sulfide solid electrolyte having a reduction reaction peak at 0.3 V (vs Li / Li) in a cyclic voltammetry measurement. + ) and above 1.0V(vsLi / Li +) or less sulfide solid electrolyte having no reduction reaction peak. In the solid electrolyte layer A, the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte is greater than 0 wt % and less than 45 wt %. Through the charging step, a protective layer containing Li and M is formed between the negative electrode current collector and the solid electrolyte layer A.
[0068] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any technical solution having substantially the same structure and achieving the same effect as the technical idea described in the patent claims of the present disclosure is included in the technical scope of the present disclosure.
[0069] Example 1
[0070] Preparation of sulfide solid electrolyte
[0071] As the starting materials of the first sulfide solid electrolyte, Li2S, P2S5 and SnS2 were prepared. These starting materials were mixed in a ball mill (mechanical grinding) and sintered to obtain Li2S with an LGPS type crystal phase. 10 SnP2S 12 (First sulfide solid electrolyte) Next, Li2S, P2S5 and LiI were prepared as starting materials for the second sulfide solid electrolyte. These starting materials were mixed (mechanically ground) and sintered in a ball mill to obtain Li3PS4 containing LiI (second sulfide solid electrolyte).
[0072] Preparation of composite materials for solid electrolyte layer
[0073] The first sulfide solid electrolyte and the second sulfide solid electrolyte were weighed so that the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 10% by weight, and they were mixed in a mortar. Thus, a composite material for solid electrolyte layer A was obtained. In addition, the second sulfide solid electrolyte was prepared as a sulfide solid electrolyte for solid electrolyte layer B.
[0074] Preparation of positive electrode
[0075] In a polypropylene container, butyl butyrate, a 5 wt% butyl butyrate solution of a polyvinylidene fluoride-based binder, lithium nickel cobalt aluminum oxide, the above-mentioned second sulfide solid electrolyte, and vapor-grown carbon fiber (VGCF) were added. The polypropylene container was recorded as a PP container. Vapor-grown carbon fiber (VGCF) is a conductive material. Lithium nickel cobalt aluminum oxide is a positive electrode active material. The volume ratio of the positive electrode active material and the second sulfide solid electrolyte was set to positive electrode active material: second sulfide solid electrolyte = 75:25. Next, the PP container was stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, the PP container was vibrated for 30 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) to obtain a slurry for the positive electrode active material layer. Then, using a coater, the above slurry was applied to the Al foil (positive electrode collector) using a doctor blade method. Then, it was naturally dried on a hot plate at 100°C for 30 minutes. In this way, a positive electrode including a positive electrode current collector and a positive electrode active material layer was obtained.
[0076] Preparation of negative electrode current collector
[0077] As a negative electrode current collector, Ni foil was prepared. Mg was vapor-deposited on the surface of the Ni foil to form a Mg layer (thickness 1000 nm). Thus, a negative electrode current collector having a Mg layer was obtained.
[0078] Production of battery cells
[0079] In area 1cm 2 50 mg of the second sulfide solid electrolyte for solid electrolyte layer B was placed in a Macor cylinder and heated to 1 ton / cm 2 Next, 50 mg of the composite material for solid electrolyte layer A was placed on top of solid electrolyte layer B and pressed at 1 ton / cm 2 The solid electrolyte layer A was formed by pressing with a pressure of 1 ton / cm 2 Next, the negative electrode current collector was arranged on the surface of the solid electrolyte layer A in such a way that the Mg layer and the solid electrolyte layer A faced each other, and the pressure was 6 tons / cm 2 The laminated body obtained by pressing was connected to a positive terminal and a negative terminal, and was restrained with a pressure of 2 N·m to obtain a battery cell. The number of layers of the solid electrolyte layer in the obtained battery cell was 2.
[0080] Example 2
[0081] A battery cell was obtained in the same manner as in Example 1 except that a composite material was used for solid electrolyte layer A in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 30 wt %. The number of solid electrolyte layers in the obtained battery cell was two.
[0082] Example 3
[0083] A battery cell was obtained in the same manner as in Example 1 except that a composite material for solid electrolyte layer A was used in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 40 wt %. The number of solid electrolyte layers in the obtained battery cell was two.
[0084] Comparative Example 1
[0085] The amount of the composite material used for the solid electrolyte layer A was changed from 50 mg to 100 mg. No solid electrolyte layer B was formed, and as the composite material for the solid electrolyte layer A, a composite material was used in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 0 weight %. Except for this, a battery cell was obtained in the same manner as in Example 1. The number of layers of the solid electrolyte layer in the obtained battery cell was 1.
[0086] Comparative Example 2
[0087] A battery cell was obtained in the same manner as in Comparative Example 1 except that a composite material was used for solid electrolyte layer A in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 40 wt %. The number of solid electrolyte layers in the obtained battery cell was one.
[0088] Comparative Example 3
[0089] A battery cell was obtained in the same manner as in Comparative Example 1 except that a composite material for solid electrolyte layer A was used in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 50 wt %. The number of solid electrolyte layers in the obtained battery cell was one.
[0090] Comparative Example 4
[0091] A battery cell was obtained in the same manner as in Comparative Example 1 except that a composite material was used for solid electrolyte layer A in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 100 wt %. The number of solid electrolyte layers in the obtained battery cell was one.
[0092] Comparative Example 5
[0093] A battery cell was obtained in the same manner as in Example 1 except that a composite material was used for solid electrolyte layer A in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 50 wt %. The number of solid electrolyte layers in the obtained battery cell was two.
[0094] Reference Example 1
[0095] A battery cell was obtained in the same manner as in Comparative Example 1 except that a composite material for solid electrolyte layer A was used in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 5 wt %. The number of solid electrolyte layers in the obtained battery cell was one.
[0096] Reference Example 2
[0097] A battery cell was obtained in the same manner as in Comparative Example 1 except that a composite material for solid electrolyte layer A was used in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 10 wt %. The number of solid electrolyte layers in the obtained battery cell was one.
[0098] Reference Example 3
[0099] A battery cell was obtained in the same manner as in Comparative Example 1 except that a composite material for solid electrolyte layer A was used in which the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte was 30 wt %. The number of solid electrolyte layers in the obtained battery cell was one.
[0100] evaluate
[0101] Cyclic voltammetry
[0102] The first sulfide solid electrolyte (Li 10 SnP2S 12 ) and the second sulfide solid electrolyte (Li3PS4 containing LiI), and cyclic voltammetry (CV) was performed. As a sample for measurement, a mixture of a sulfide solid electrolyte and a conductive material (VGCF) was prepared on stainless steel (SUS), and a sample (thickness 1mm) of Li foil was stacked on the mixture. CV measurement was performed at a scan rate of 1mV / sec. As a result, it was confirmed that the first sulfide solid electrolyte (Li 10 SnP2S 12 ) at 0.3V(vsLi / Li +) and above 1.0V(vsLi / Li + ) has a reduction reaction peak below 0.3 V (vs Li / Li + ) and above 1.0V(vsLi / Li + ) and below do not have a reduction reaction peak.
[0103] Evaluation of cycle characteristics
[0104] The battery cells obtained in each embodiment, each comparative example and each reference example were subjected to the conditions of temperature 25°C, voltage range 3.0 V to 4.2 V, CCCV mode, current value 0.6 mA / cm 2 (0.03mA / cm 2 The charge and discharge measurements were carried out under the conditions of 1 cycle and 20 cycle. The capacity retention rate (%) was calculated from the discharge capacity of the 1st cycle and the discharge capacity of the 20th cycle. The results are shown in Tables 1 and Figure 4 .
[0105] Table 1
[0106]
[0107] As shown in Table 1 and Figure 4 As shown, it is confirmed that Examples 1 to 3 have a higher capacity retention rate than Comparative Examples 1 to 4, and good cycle characteristics are obtained. In addition, when comparing Comparative Example 1 and Comparative Example 4, the capacity retention rate of Comparative Example 4 is significantly lower than that of Comparative Example 1. It is speculated that this is because the first sulfide solid electrolyte (Li 10 SnP2S 12 ) has a lower reduction resistance than the second sulfide solid electrolyte (Li3PS4 containing LiI). On the other hand, although Comparative Example 1 and Reference Examples 1 to 3 are compared, Reference Examples 1 to 3 contain a first sulfide solid electrolyte with relatively low reduction resistance, the capacity retention rate is high compared to Comparative Example 1. It is speculated that this is because the reactant of the first sulfide solid electrolyte and Li (especially LiM alloy) functions as a protective layer. In addition, Comparative Example 1 is compared with Comparative Examples 2 and 3, and the capacity retention rate of Comparative Examples 2 and 3 is reduced compared to Comparative Example 1. It is speculated that this is because the reactant of the first sulfide solid electrolyte and Li functions as a resistance layer instead.
[0108] Comparing Example 1 with Reference Example 2, Example 1 has a higher capacity retention rate than Reference Example 2. Similarly, comparing Example 2 with Reference Example 3, Example 2 has a slightly higher capacity retention rate than Reference Example 3. It was confirmed that by constituting the solid electrolyte layer with a plurality of layers in this way, a first sulfide solid electrolyte having relatively low reduction resistance is biased toward the layer on the negative electrode current collector side, and a good capacity retention rate is also obtained.
[0109] Comparing Reference Example 1 with Comparative Example 1, Reference Example 1 has a higher capacity retention rate than Comparative Example 1. This result and the tendency of Examples 1, 2 and Reference Examples 2, 3 mentioned above suggest that a good capacity retention rate is also obtained in the following cases. The so-called following case is a case where the solid electrolyte layer has a solid electrolyte layer A and a solid electrolyte layer B, and in the solid electrolyte layer A, the ratio of the first sulfide solid electrolyte to the total of the first sulfide solid electrolyte and the second sulfide solid electrolyte is 5% by weight. In addition, comparing Comparative Example 3 with Comparative Example 5, Comparative Example 5 has a higher capacity retention rate than Comparative Example 3, but a lower capacity retention rate than Comparative Example 1. It is speculated that this is because, as described above, the reactant of the first sulfide solid electrolyte and Li functions as a resistance layer instead.
[0110] Reference Example 4
[0111] Preparation of sulfide solid electrolyte
[0112] In the same manner as in Example 1, Li3PS4 (a second sulfide solid electrolyte) containing LiI was obtained.
[0113] Fabrication of solid electrolyte layer
[0114] Heptane, a 5 wt% heptane solution of a polyvinylidene fluoride binder, and the above-mentioned second sulfide solid electrolyte were added to a polypropylene container (PP container). Next, the PP container was stirred for 30 seconds using an ultrasonic disperser (UH-50 manufactured by SMT). Next, the PP container was vibrated for 30 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) to obtain a slurry for a solid electrolyte layer. Then, using a coater, the slurry was applied to a PET film using a doctor blade method. Then, it was naturally dried on a hot plate at 100°C for 30 minutes. After drying, two coated solid electrolyte layers were prepared, bonded to each other, and heated with 7 tons / cm 2 After pressing, the PET film was peeled off to obtain an independent (self-supporting) solid electrolyte layer. Furthermore, a Sn layer (thickness 100 nm) was formed on one side of the solid electrolyte layer by sputtering.
[0115] Preparation of positive electrode
[0116] In the same manner as in Example 1, a positive electrode was obtained.
[0117] Preparation of negative electrode current collector
[0118] In the same manner as in Example 1, a negative electrode current collector having a Mg layer was obtained.
[0119] Battery cell manufacturing
[0120] The negative electrode collector having the Mg layer and the solid electrolyte layer having the Sn layer were punched into φ14.5 mm, respectively. Secondly, the negative electrode collector and the solid electrolyte layer were stacked in a manner that the Mg layer and the Sn layer were opposite to each other. Secondly, a positive electrode punched into φ11.28 mm was arranged on the solid electrolyte layer. The positive terminal and the negative terminal were connected to the obtained stack and sealed with a stacking film. For the sealed stack, cold isostatic pressing (CIP) treatment was performed at a pressure of 392 MPa. Then, the CIP-treated stack was constrained with a metal plate at a pressure of 1 MPa to obtain a battery cell.
[0121] Reference Examples 5 to 7
[0122] A battery cell was obtained in the same manner as in Reference Example 4 except that sputtering of Al, Zn or In was performed instead of sputtering of Sn when the solid electrolyte layer was produced.
[0123] Reference Example 8
[0124] A battery cell was obtained in the same manner as in Reference Example 4 except that sputtering was not performed when the solid electrolyte layer was produced.
[0125] evaluate
[0126] The battery cells obtained in the respective reference examples were subjected to charge and discharge measurements in the same manner as described above, and the capacity retention rate (%) was determined. The results are shown in Table 2.
[0127] Table 2
[0128]
[0129] As shown in Table 2, Reference Examples 4 to 7 were confirmed to have higher capacity retention rates and better cycle characteristics than Reference Example 8. It is speculated that the metals used in Reference Examples 4 to 7 are all metals that can be alloyed with Li, and they are alloyed with Li during charging to function as a protective layer, thereby increasing the capacity retention rate. This suggests that even when the first sulfide solid electrolyte contains the above metal, similarly good cycle characteristics can be obtained.
Claims
1. All-solid-state battery is an all-solid-state battery that uses the precipitation and dissolution reaction of metallic lithium as the negative electrode reaction. It has a negative electrode collector, a solid electrolyte layer A, a solid electrolyte layer B and a positive electrode active material layer in the thickness direction. The solid electrolyte layer A contains a first sulfide solid electrolyte and a second sulfide solid electrolyte, The solid electrolyte layer B contains a third sulfide solid electrolyte, The first sulfide solid electrolyte is measured at 0.3V (vsLi / Li + ) and above 1.0V(vsLi / Li + ) or less sulfide solid electrolyte having a reduction reaction peak, and containing M element, M is at least one of Sn, Al, Zn, In, Ge, Si, Sb, Ga and Bi, The second sulfide solid electrolyte is measured at 0.3V (vsLi / Li + ) and above 1.0V(vsLi / Li + ) or less sulfide solid electrolyte having no reduction reaction peak, In the solid electrolyte layer A, a ratio of the first sulfide solid electrolyte to the total weight of the first sulfide solid electrolyte and the second sulfide solid electrolyte is greater than 0 weight % and 45 weight % or less.
2. The all-solid-state battery according to claim 1, wherein: In the solid electrolyte layer A, a ratio of the first sulfide solid electrolyte relative to the total weight of the first sulfide solid electrolyte and the second sulfide solid electrolyte is 5% by weight or more and 40% by weight or less.
3. The all-solid-state battery according to claim 1, wherein: The third sulfide solid electrolyte is measured at 0.3V (vsLi / Li + ) and above 1.0V(vsLi / Li + ) or less sulfide solid electrolyte having no reduction reaction peak.
4. The all-solid-state battery according to claim 1, wherein: The first sulfide solid electrolyte contains Li element, the M element, and S element, and the M element is at least one of Sn, Al, Zn, and In.
5. The all-solid-state battery according to claim 1, wherein: The all-solid-state battery has a protective layer containing Li and M between the negative electrode collector and the solid electrolyte layer A.
Citation Information
Patent Citations
All-solid battery
JP2021089814A